2015
DOI: 10.1002/2015gl065626
|View full text |Cite
|
Sign up to set email alerts
|

Charge and discharge of polar cold air mass in northern hemispheric winter

Abstract: This study shows the variability of polar cold air mass amount below potential temperature of 280 K, and north of 45°N can be understood with a concept of charge and discharge, where anomalously large daily discharge indicates an intermittent occurrence of cold air outbreak. The polar cold air mass amount north of 45°N gradually charges up due to diabatic cooling but dramatically discharges due to cold air outbreak with a pulse width of about 5 days. Cold air outbreaks tend to bring colder winter in East Asia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 35 publications
(60 reference statements)
0
25
0
Order By: Relevance
“…The polar cold air mass (PCAM) grows over high latitudes, outflows equatorward, and then disappears at lower latitudes (Iwasaki et al, ; Iwasaki & Mochizuki, ; Kanno, Abdillah, & Iwasaki, ). The outbreaks of the PCAM dominate wintertime weather and can cause severe damages to society (Cellitti et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The polar cold air mass (PCAM) grows over high latitudes, outflows equatorward, and then disappears at lower latitudes (Iwasaki et al, ; Iwasaki & Mochizuki, ; Kanno, Abdillah, & Iwasaki, ). The outbreaks of the PCAM dominate wintertime weather and can cause severe damages to society (Cellitti et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of the hemispheric PCAM can be diagnosed by a zonal‐mean two‐box model (Kanno, Shoji, & Iwasaki, , hereafter KS15). By considering a genesis box at high latitudes and a loss box at low latitudes, the two‐box model effectively explains the charge‐discharge theory of the hemispheric‐scale PCAM (Kanno, Abdillah, & Iwasaki, ; hereafter KA15). It has been found that the total PCAM depends on the residence time of the PCAM in the genesis box (KS15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Kanno et al . [] studied the detrended interannual variability of the CAM for the NH winter based on a charge‐discharge theory. The CAM flux across 45°N decreases the CAM at higher latitudes but increases the CAM at lower latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…The average lifetime of the CAM in the NH winter has been estimated to be approximately 25 days based on a two-box model [Kanno et al, 2015a]. Furthermore, Kanno et al [2015b] studied the detrended interannual variability of the CAM for the NH winter based on a charge-discharge theory. The CAM flux across 45°N decreases the CAM at higher latitudes but increases the CAM at lower latitudes.…”
Section: Introductionmentioning
confidence: 99%